Maintenance management success factors for heritage building: a framework - Akasah, Z. A.; A. Abdul, R. M.; F. Zuraidi, S. N. (WIT Pres, 2011)
This paper attempts to establish a theoretical framework for maintenance management success factors in managing built heritage. Reviews on past literature on the subject were carried out to build the existing research works on the area and to establish critical success factors of built heritage maintenance management best practices. At the end of this paper, a new area of managing heritage building for future direction of this research was identified. A list of critical success factors for maintenance management practices for heritage building was established.